ANALISIS PENGARUH INOVASI PRODUK TERHADAP KEPUASAN KONSUMEN DENGAN KEUNGGULAN BERSAING SEBAGAI VARIABEL INTERVENING PADA PRODUK GULA PASIR SEBELAS (GUPALAS) PABRIK GULA SEMBORO PTP NUSANTARA XI (PERSERO) - Sukarmen, Putu; Sularso, R. Andi; Wulandri, Deasy (Universitas Jember, 2013)
This study aimed to examine the effect of product innovation on consumer satisfaction with a competitive advantage as an intervening variable in sugar products (Gupalas) at Sugar Factory Semboro PTP Nusantara XI (Persero). In this study there are three hypotheses, namely product innovation affect customer satisfaction, product innovation affect the competitive advantage and competitive advantage effect on customer satisfaction. Consumer research population is the end gupalas in Jember. By using a sampling technique Purpusive Sampling, obtained 173 respondents was conducted in January and February 2013. The analysis usedis Confirmatory Regression Analysis. Having proven valid and reliable and test the feasibility of the model that has been proven to be good. Then conducted confirmatory regression test with significance